Firestorm - Barr, Nevada (New York Avon Books, 1997)
A raging forest fire in California's Lassen Volcanic National Park traps exhausted firefighters, including Ranger Anna Pigeon, in its midst. Afterward, Anna finds two from her group have been killed. One a victim of the flames. The other, stabbed through the heart. Now, as a rampaging winter storm descends, cutting the survivors off from civilization, Anna must uncover the murderer in their midst.
Keywords: Women park rangers -- Detective and mystery stories -- Fire fighters